MANAJEMEN PENINGKATAN TATA KELOLA MADRASAH BERMUTU (Studi Deskriptif pada MAS Aliyah Baitul Huda dan MAS Al-Fatah Swasta di Kabupaten Bandung) - N.Yaqin; Iim Wasliman; Waska Warta (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
The title of this research is ”management to improve quality madrasah governance (descriptive study on private madrasah aliyah in bandung district)” this title was chosen because it wanted to reveal how madrasah apply the management principles of madrasah governance, thus giving birt to quality madrasah, increasing graudates and having high competitiveness. Research objectives: in general, is to examine strategies for improving governance in private madrasah aliyah in the kertasari sub-district, bandung district in implementing the ministry of education regulation. In order to improve quality education. And specific objectives. (1) to determine the planning of quality madrasah governance programs in private madrasah aliyah in kertasari sub-district, (2) implementation of programs on quality madrasah governance, (3) supervision of quality madrasah governance programs, (4) problems about quality madrasah governance programs, (5) efforts to improve the madrasah governance programs. Whhereas in the process of extracting the results of the filed the author uses the triangulation of results, namely: interview, obsevation ,dokumentation study.in two madrasah that are catagorized as high-quality madrasah, namely the baitul huda joglo alyah madrasah, kertasari sub-district, bandung district and islamic school aliyah al-fatah sukasari kertasari sub-district, bandung district. Basedvon the results of the study, it was found, among others:(1) quality madrasah management planning in the two madrasah was to combine religious and general sciences, as well as the eistence of other programs, such as educational programs and social programs. (2) the implementation of quality management of madrasah governance at the two institutions is related to improving the quality of education which refers to the national ducation standars that must be comprehensive and consequently about the management of education carried out by madrasah citizens. (3)supervision of qulity madrasah governance at these institutions is carried out in a thorough manner, meaning that suvervision is inherent in every educational actor in the two institutions. (4) follow-up madrasah governance faced by the two institutions includes providing direction and understanding to the community about madrasa, so that they are moren inrested in and support the madrasah programs. (5) efforts to improve madrasah management program are faced by the two institutions in the future by increasing collaboration with various related parties.